Coexpression of PD-L1/PD-1 with CXCR3/CD36 and IL-19 Increase in Extranodal Lymphoma - Manal Mohamed Saber (Journal of Immunology Research)
Many studies have demonstrated that PD-L1/PD-1 signaling is an immune evasion mechanism in tumors. PD-L1/PD-1 coexpression with CXCR3/CD36 in peripheral lymphocytes in lymphoma still needs to be clarified. The current study investigated PD-L1/PD-1 coexpression with CXCR3/CD36 in circulating lymphocytes, serum IL-19 levels, and their correlation with clinical outcome and extranodal involvement in lymphoma. Subjects and Methods. The coexpression of PD-L1/PD-1 with CXCR3/CD36 on circulating lymphocytes was analyzed by flow cytometry in 78 lymphoma patients before and after therapy and in 50 healthy controls. The concentration levels of IL-19 in serum were assessed by an ELISA. Results. PD-L1 and PD-1 were expressed on circulating CXCR3+ and CD36+ lymphocytes in lymphoma and were significantly higher in patients with extranodal involvement than in lymphoma patients without extranodal involvement (P<0.001). Elevated IL-19 levels were observed in lymphoma patients and increased significantly in extranodal involvement (P<0.001). High percentages of PD-L1+CXCR3+ and PD-1+CXCR3+ lymphocytes were associated with high LDH levels, hepatomegaly, lymphedema, advanced tumor stage, and recurrence. Furthermore, patients with splenomegaly and generalized lymphadenopathy had high percentages of PD-L1+CXCR3+ lymphocytes. In addition, levels of PD-L1/PD-1 coexpression with CXCR3 and IL-19 were significantly associated with bone marrow, lung, and lymph vessel involvement. Further analysis revealed that high percentages of PD-L1+CD36+ and PD-1+CD36+ lymphocytes were associated with lung and bone marrow involvement. Patients with high levels of PD-L1/PD-1 coexpression with CXCR3 and IL-19 had inferior event-free survival (EFS) compared with that in lymphoma patients with low levels. EFS was decreased in patients with high percentages of PD-L1+CD36+ and PD-1+CD36+ lymphocytes. When using the receiver operating characteristic (ROC) curve, the superiority of IL-19 (area under the curve (AUC): 0.993) and PD-L1+CXCR3+% (AUC: 0.961) to PD-1+CXCR3+% (AUC: 0.805), PD-L1+CD36+% (AUC: 0.694), and PD-1+CD36+% (AUC 0.769) was evident in the diagnosis of extranodal involvement, identifying lymphoma patients with extranodal involvement from patients without extranodal involvement. Conclusions. Coexpression of PD-L1/PD-1 with CXCR3/CD36 in circulating lymphocytes and serum IL-19 levels contributes to poor prognosis and might be potential markers for extranodal involvement in lymphoma.